The Effect of Applying the Ethno-STEM-Project-based Learning Model on Students' Higher-order Thinking Skill and Misconception of Physics Topics Related to Lake Tempe, Indonesia - Martawijaya, M. A.; Rahmadhanningsih, S.; Swandi, A.; Hasyim, M.; Sujiono, E. H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to determine the effect of applying the Ethno-STEM-Project Based Learning model about the concept of physics related to Lake Tempe on students’ conceptual understanding of physics, which is characterized by higher-order thinking skills and the level of misconceptions. The sample in this study was eleventh-grade students in senior high school. Students are exposed to local wisdom-based learning strategies integrating science, technology, engineering, and mathematics through group project assignments. Students are given a pre-Achievement Test (PAT) to determine their initial Higher-Order Thinking Skill of physics concepts in everyday life. Then after being treated through project work, they are asked to do a Post-Achievement Test (PAT). A three-tier test was carried out before and after treatment to determine the level of misconceptions. In addition, focus group interviews were conducted with several students to strengthen the pre and post-test results. Student responses to focus group interviews and the PAT’s open-ended questions were analyzed using the N-Gain Score equation. The data in the initial and final tests were analyzed quantitatively and qualitatively. Based on the analysis results, it was found that using the Ethno-STEM-PjBL model affected the understanding of physics concepts. It was marked by increases in higher-order thinking skills and decreases in misconceptions on several physics topics related to students’ activities around Lake Tempe.